સમીકરણ $\sqrt {(x + 10)} + \sqrt {(x - 2)} = 6$ નો ઉકેલ મેળવો.
$0$
$6$
$4$
એકપણ નહીં
$\sqrt {(3 + \sqrt 5 )} = . .$ .
જો $x = {{\sqrt 5 + \sqrt 2 } \over {\sqrt 5 - \sqrt 2 }},y = {{\sqrt 5 - \sqrt 2 } \over {\sqrt 5 + \sqrt 2 }},$ તો $3{x^2} + 4xy - 3{y^2} = $
જો $a = \sqrt {(21)} - \sqrt {(20)} $ અને $b = \sqrt {(18)} - \sqrt {(17),} $ તો
જો ${x^{x\root 3 \of x }} = {(x\,.\,\root 3 \of x )^x},$ તો $x = .. . .$
${{3\sqrt 2 } \over {\sqrt 6 + \sqrt 3 }} - {{4\sqrt 3 } \over {\sqrt 6 + \sqrt 2 }} + {{\sqrt 6 } \over {\sqrt 3 + \sqrt 2 }} = $